2005
DOI: 10.1007/s10804-005-2485-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research in Puebla Prehistory

Abstract: Puebla art style. Not only do these topics illustrate the scope of archaeological work, but they can be linked to broader anthropological themes like the origins and spread of agriculture, relationships between rural populations and emergent cities, the environmental, social, and cultural impact of natural disasters, the operation of geographical frontiers and ethnic interfaces, the construction of cultural landscapes, and the connections between political organization and art style. Puebla's location along nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 49 publications
1
29
0
1
Order By: Relevance
“…It is possible that this turmoil may have created a flux of migrants to other rising centers of regional power (18,20). Cantona is similar to other regional powers that emerged in the late Classic, because it is strategically located, on a basaltic flow with a view of the surrounding landscape (2,10,18). This defensible position may have contributed to the site's persistence, and might have helped the city attract migrants fleeing political turmoil.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is possible that this turmoil may have created a flux of migrants to other rising centers of regional power (18,20). Cantona is similar to other regional powers that emerged in the late Classic, because it is strategically located, on a basaltic flow with a view of the surrounding landscape (2,10,18). This defensible position may have contributed to the site's persistence, and might have helped the city attract migrants fleeing political turmoil.…”
Section: Resultsmentioning
confidence: 95%
“…Paleoclimate records from this area therefore have broad implications for our understanding of the importance of past climate change in altering the "northern frontier of Mesoamerica," defined as the northern limit of maize agriculture (9). Moreover, this area was controlled by powerful pre-Columbian city-states in the Classic and Post-Classic periods, and served as an important site of contact between highland Mexico and the cultures of the Atlantic Gulf Coast (10).…”
mentioning
confidence: 99%
“…It is also worth considering the wide variety of examples of material reuse and recycling documented in the archaeological record. Several ethnographic and archaeological studies have identified the stockpiling of discards as an indicator of reuse and recycling behaviors (Bradley, 1988;Chang, 1988Chang, , 1991Hayden and Cannon, 1983;Kamp, 1991;Pettegrew, 2002;Plunket and Uruñuela, 2005;. Other studies have documented that systematic scavenging and reclamation can commonly occur at abandoned structures (Cameron, 1990(Cameron, , 1991Diehl, 1998;Tomka 1993).…”
Section: Reclamation and Recycling In The Archaeological Recordmentioning
confidence: 99%
“…Nevertheless, in domestic areas on the periphery of Cholula, fragments of these vessels have been found in trash pits and building lls (Hernández 2005:42;Suárez et al 1992). is suggests that not only a restricted sector of the population had access to them, although the nature of these Cholultecan domestic deposits still requires more analysis (see Plunket and Uruñuela 2005). e events represented by those archaeological remains -public ceremonies, feasts, o erings and funerary rituals-were, and still are, essential elements of community life in Mesoamerica.…”
Section: Ceramics As Ritual Objects and Media Of Literacymentioning
confidence: 99%